FEASIBILITY OF A COMPETENCY-BASED SKILLS ASSESSMENT BOOK FOR THE SUBJECT OF BIOLOGY IN GRADE VIII JUNIOR HIGH SCHOOL - Ningsih, Kurnia; Afandi, Afandi (Universitas Tanjungpura, 2024)
This study is intended to determine the feasibility and teacher response to competency-based skills assessment book products in Science-Biology subjects in Class VIII Junior High School. The research method used is Research and Development through 7 stages, namely; (1) potential and problems, (2) data collection, (3) product design, (4) product design validation, (5) product design revision, (6) product trial, and (7) product revision. The research instrument was a product feasibility assessment sheet and a response questionnaire in the form of a Likert scale. Product feasibility was assessed by five experts. The data obtained from the validation sheet (feasibility) was analyzed using Aiken's formula. The product trial was conducted on six teachers. The results showed that the feasibility of the product and the response questionnaire assessed by the validators obtained results respectively were 0.97 and 0.99 with high validity and feasible to use. After the trial, the teacher's response to the competency-based skills assessment book was stated to be very good with an average value of 95.00%. It can be concluded that the book product made is feasible to use for competency-based skills assessment with a very good response.